Structural and functional characteristics of soil microbial communities in response to different ecological risk levels of heavy metals - Li, Dale; Chen, Jianwen; Zhang, Xiujuan; Shi, Wei; Li, Junjian (Frontiers in Microbiology, 2022)
Microbial information in the soil can be used as an indicator for heavy metals (HMs) risk evaluation. Our previous study has shown that microbial abundance and diversity are not considerably different among samples treated with various concentrations of lead (Pb) and cadmium (Cd) at the same risk level. However, little is known about the responses of microbial community structures and functions to HMs at different risk levels. In this study, soil microcosm experiments with low (L), medium (M), and high (H) ecological risk levels, depending on the Pb and Cd concentrations, were conducted. The original soil was used as the control (CK). High-throughput sequencing, qPCR, and Biolog plate approaches were applied to investigate microbial community structures, abundance, diversity, metabolic capacity, functional genes, and community assembly processes. The abundance and alpha diversity indices for bacteria at different risk levels were significantly lower than those of the CK. Meanwhile, the abundance and ACE index for the fungi increased significantly with risk levels. Acidobacteria, Basidiomycota, and Planctomycetes were enriched as the risk level increased. Keystone taxa and co-occurrence pattern analysis showed that rare taxa play a vital role in the stability and function of the microbial community at different risk levels. Network analysis indicates that the complexity and vulnerability of microbial community decrease with increasing risk levels. The lowest number of keystone taxa was found at the H level. However, the microbial community showed enhanced intraspecific cooperation to adapt to HMs stress. The Biolog plate data indicated that the average well color development (AWCD) was significantly reduced with risk levels in bacteria. Meanwhile, fungal AWCD only showed a substantial reduction at the H level. Functional diversity indices and gene abundance for microorganisms at the H level were significantly lower than those of the CK. Microbial community assembly tended to be more stochastic with an increase in risk levels. These results provide new insights into the ecological impacts of HMs on the soil microbiome at different risk levels and will aid in future risk assessments for Pb and Cd contamination.